PENERAPAN PERSONNEL DAN CULTURAL CONTROL BERBASIS NILAI SPIRITUAL DALAM MENGATASI CONTROL PROBLEMS PADA GRAMEDIA ROYAL PLAZA, SURABAYA - Juniar Komara (CALYPTRA, 2018)
Absract- This research aims to explain the relationship between the application of values in the control system which is personneland cultural control to resolve control problems. This research specifically wanted to find out how spiritual values affect personnel and cultural control as informal control system. The spiritual value can affect informal control system to resolve control problems that exist. This type of research is applied research with a qualitative approach. This reseach seeks to provide recommendations to the control problems by implementation of spiritual values that has not been fully implemented. The research found that there are five control problems at Gramedia Royal Plaza, Surabaya. Control problems occur due to weak informal control system. Spiritual values i n informal control system for help organization more maximum achieve the goal.